Tetrabdella neotropica (Acari: Bdellidae), a new genus and species from Brazil - Hernandes, Fabio A. [UNESP]; Feres, Reinaldo J. F. [UNESP] (My University, 2006)
Tetrabdella neotropica Hernandes & Feres n. gen., n. sp. is the first representative of the family Bdellidae from South America. It can be distinguished from other bdellid mites by the presence of two trichobothriae on tarsi III and IV. The subfamily Spinibdellinae is herein redefined to accomodate the new genus. A key to world genera of Bdellidae is presented. Copyright © 2006 Magnolia Press.
Keywords: Acari; Asymmetry; Hevea brasiliensis; Mites; Neotropical; New genus; Prostigmata; Bdellidae